Criminological Aspects Regarding the Smuggling of Counterfeit Products. Ways of Legal and Criminal Protection at European Level: Array - Ștefănuț, Radu (Journal of Danubian Studies and Research, 2020)
The object of the topic is represented by the analysis of criminogenic factors that generate and facilitate smuggling in the Eastern part of the European Union, a phenomenon in which a main place is occupied by counterfeit products. The result sought is given by the identification of the sides and the highlighting of the criminogenic elements, many of them related to organized crime, which obtain huge profits by carrying out the criminal activity of smuggling. The conclusion consists in identifying and dynamizing the juridical-criminal ways of cooperation in order to combat the phenomenon of cross-border smuggling of counterfeit products.